Nutrition for human performance - Close, G. L.; Morton, J. P. (Strength and conditioning for sports performance, 2016)
Sports nutrition is becoming increasingly recognised as one of the most important sub-disciplines of strength and conditioning (S&C). In the UK, sports nutritionists (commonly referred to as performance nutritionists or sports dieticians if the practitioner is clinically trained) usually work on a consultancy basis, although there are now an increasing number of sporting clubs and organisations that employ individuals on a full-time basis. This trend for increased employment opportunities probably represents the increased recognition from staff within professional sport that sound nutrition has a key role to plav in maximising performance and promoting training adaptation and recovery. Regardless of the exact employment status or career pathway to entering the profession, we consider that all sports nutritionists should operate within a multidisciplinary team (e.g. coaches, doctors, physiotherapists, S&C professionals, sport scientists, chefs, etc.) and share common aims and objectives. In the authors` opinion, the sports nutritionist should aim to provide scientifically sound and individualised nutritional interventions that maximise performance, promote training adaptations and recovery whilst maintaining well-being and increasing athlete education at all times. This chapter provides an overview of sports nutrition issues that are the most relevant to S&C coaches. Owing to space constraints, it is not possible to discuss all research developments in the field. Nevertheless, we review both classical and contemporary literature and discuss the macronutrient (carbohydrates, protein and fats), micronutrient (vitamins and minerals) and hydration (fluid) requirements for training and competition as well as outlining ergogenic aids (sports supplements) which may aid performance and training adaptations. In keeping with contemporary issues, we close by discussing (by drawing upon the discipline of molecular biology) how nutritional manipulation can modify training adaptations through exercise-nutrient gene interactions.